Upregulation of microRNA‐218 reduces cardiac microvascular endothelial cells injury induced by coronary artery disease through the inhibition of HMGB1. Issue 3 (30th September 2019) - Gao, Wenhui; Cui, Hanbin; Li, Qianjun; Zhong, Hai; Yu, Jingjing; Li, Ping; He, Xijie
Abstract: This study is performed to examine the impacts of microRNA‐218 (miR‐218) on cardiac microvascular endothelial cells (CMECs) injury induced by coronary artery disease (CAD). Reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) was applied for detecting miR‐218 expression in serum of patients with CAD and healthy controls, and the correlation between miR‐218 expression and the clinical indexes such as creatine kinase, creatine kinase‐myocardial band, cardiac troponin I, and coronary Gensini score was analyzed. CMECs were coincubated with homocysteine for 24 hr for CMECs injury, and the cells were transfected with miR‐218 mimics or miR‐218 inhibitors. Besides, we used oxidized low density lipoprotein as an inducer to incubate with CMECs for 24 hr, and the model of CMECs injury was established to be transfected with miR‐218 mimics. RT‐qPCR and western blot analysis were used to detect miR‐218 and HMGB1 expression in CMECs. A series of experiments were used to determine cell proliferation, apoptosis, migration, and angiogenesis ability of CMECs. Vascular endothelial growth factor expression and inflammatory factor contents were measured. The obtained results suggested that miR‐218 expression in peripheral blood of patients with CAD descended substantially versus that of healthy controls. Low miR‐218 expression was found in CAD‐induced CMECs injury. Overexpressed miR‐218 promoted the proliferation, migration, angiogenesis ability, induced apoptosis, and alleviated the inflammatory injury of CAD‐induced CMECs. miR‐218 may negatively regulate the expression of HMGB1 in CAD. This study demonstrates that upregulation of miR‐218 reduces CMECs injury induced by CAD through the inhibition of HMGB1.